2021
DOI: 10.1016/j.ymeth.2020.10.005
|View full text |Cite
|
Sign up to set email alerts
|

A correlative super-resolution protocol to visualise structural underpinnings of fast second-messenger signalling in primary cell types

Abstract: Nanometre-scale cellular information obtained through super-resolution microscopies are often unaccompanied by functional information, particularly transient and diffusible signals through which life is orchestrated in the nano-micrometre spatial scale. We describe a correlative imaging protocol which allows the ubiquitous intracellular second messenger, calcium (Ca 2+ ), to be directly visualised against nanoscale patterns of the ryanodine receptor (RyR) Ca 2+ channels which give rise to these Ca 2+ signals i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 49 publications
(58 reference statements)
0
29
0
Order By: Relevance
“… Fu et al (2016) have observed that RyRs phosphorylated at S2808 more readily colocalize with LTCCs, and in a manner that requires bridging integrator 1 (BIN1). This intriguing finding suggests that S2808-phosphorylated RyR molecules are recruited to the dyad; an observation that appears to be supported by higher resolution imaging studies that have tracked phosphorylated and dephosphorylated RyR ( Sheard et al, 2019 ; Hurley et al, 2021 ).…”
Section: The Complementary History Of Imaging and Computation In Card...mentioning
confidence: 75%
See 1 more Smart Citation
“… Fu et al (2016) have observed that RyRs phosphorylated at S2808 more readily colocalize with LTCCs, and in a manner that requires bridging integrator 1 (BIN1). This intriguing finding suggests that S2808-phosphorylated RyR molecules are recruited to the dyad; an observation that appears to be supported by higher resolution imaging studies that have tracked phosphorylated and dephosphorylated RyR ( Sheard et al, 2019 ; Hurley et al, 2021 ).…”
Section: The Complementary History Of Imaging and Computation In Card...mentioning
confidence: 75%
“…Specifically, the super-resolution imaging techniques described above generally require fixed cardiomyocytes, which has precluded directly pairing Ca 2+ recordings to cellular substructure. One recent study attempted this feat in a correlative manner, with sparks recorded first in live cells, prior to fixation, and subsequent super-resolution imaging of the same CRUs ( Hurley et al, 2021 ). However, it should be noted that with complex protocols for fixation, labeling, and imaging, there is considerable risk for disrupting cell geometry and alignment between imaging modalities.…”
Section: The Changing Interaction Of Experiments and Simulation In Th...mentioning
confidence: 99%
“…A major current technical challenge in optical cardiac imaging is the deterministic correlation between structural features and functional performance at different hierarchical levels, from subcellular components such as individual Ryanodine receptors (RyR) using DNA-PAINT techniques (Hurley et al, 2020 ) to single isolated CM and intact heart tissue. Assessing the structure and the corresponding local function in a correlative manner is particularly relevant in pathological settings where structural and ultra-structural alterations occur e.g., alteration of excitation-contraction coupling machinery, myofilament disarray or extracellular fibrosis.…”
Section: Correlation Of Structure and Functionmentioning
confidence: 99%
“…Julie Biteen's team have developed a new analytical tool that uses non-parametric Bayesian statistics on single-particle trajectory datasets obtained from live cell light microscopy that enables correlation of multiple mobility states, the average diffusion coefficient of single molecules in that state, the fraction of single molecules in that state, localization noise, and the probability of transitioning between states (27). Izzy Jayasinghe and colleagues have made valuable progress is development of expansion microscopy to enable the integration of TIRF imaging of Ca 2+ signals with DNA-PAINT imaging of nanoscale receptors on living primary cells that permits feature extraction and image alignment between correlative datasets for detecting ensembles of Ca 2+ channels that ere locally activated (28).…”
Section: A Next Generation Of Correlative Single-molecule Biophysics ...mentioning
confidence: 99%